A simple tool for calculating egg shape, volume and surface area from digital images. (16th July 2014) - Troscianko, Jolyon; Marsden, Stuart
<x xml:space="preserve">Abstract</x> The geometrical properties of eggs – such as volume and surface area – have uses ranging from ecological, physiological and morphological studies in birds, to predictions of chick condition in the poultry industry. Although measurements of an egg's length and breadth can be used to approximate its geometry, the coefficients used in these models are specific to the original test population, and intraspecific variation in egg shape means these methods cannot be used reliably beyond that population. Here I present a novel mathematical formula to describe the curvature of a bird's egg that can be used to calculate the shape, volume and surface area of an egg precisely from digital images. Using data from several species I demonstrate that the model has a greater level of accuracy than length‐ and breadth‐based methods, and release the user‐friendly tool for others to use for measuring eggs from digital images.